Performance analysis of a symmetric cryptography algorithm on GPU and GPU cluster - Pousa, Adrián; Sanz, Victoria María; De Giusti, Armando Eduardo (2013)
This article presents a performance analysis of the symmetric encryption algorithm AES (Advanced Encryption Standard) on a machine with one GPU and a cluster of GPUs, for cases in which the memory required by the algorithm is more than that of a GPU. Two implementations were carried out, based on C language, that use the tool CUDA in the case of a single GPU and a combination of CUDA and MPI in the case of the cluster of GPUs. The experimental work carried out shows how communications in the GPU cluster negatively affect algorithm total computation time.
Formato de archivo PDF. -- Este documento es producción intelectual de la Facultad de Informática - UNLP (Colección BIPA/Biblioteca)
Latin American Symposium on High Performance Computing (6to : 2013 jul. 29-30 : Mendoza, Argentina)
Keywords: LENGUAJE C; PROCESADORES GRÁFICOS (GPUs); arquitecturas GPUs